2018
DOI: 10.1007/jhep08(2018)081
|View full text |Cite|
|
Sign up to set email alerts
|

The β-function for Yukawa theory at large Nf

Abstract: Abstract:We compute the β-function for a massless Yukawa theory in a closed form at the order O(1/N f ) in the spirit of the expansion in a large number of flavours N f . We find an analytic expression with a finite radius of convergence, and the first singularity occurs at the coupling value K = 3.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The large N f dynamics of gauge-fermion theories has been extended to gauge-Yukawa theories starting with the Yukawa sector [25][26][27] and for the first time to all couplings in [28,29]. A gauge-less study appeared in [30]. The results widened the palette of tools and theories at our disposal for novel large N f safe extensions of the SM [7,28,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The large N f dynamics of gauge-fermion theories has been extended to gauge-Yukawa theories starting with the Yukawa sector [25][26][27] and for the first time to all couplings in [28,29]. A gauge-less study appeared in [30]. The results widened the palette of tools and theories at our disposal for novel large N f safe extensions of the SM [7,28,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…[25], there is no nontrivial fixed point in a U (1) gauge theory for N f = 4 [15]. As has been shown in the literature [13][14][15][16], the large N f models can provide other possibilities; in Ref. [13], the beta function of spinor QED has been calculated at the leading order in 1/N f , and the result suggests that there might be nontrivial (UV and IR) fixed points.…”
Section: Introductionmentioning
confidence: 68%
“…. ), which usually can be dealt with by Cauchy principal value prescription [15,16]. Assuming this prescription, it can be shown that there are a UV fixed point at g 7/2 and a symmetric IR fixed point at g 7/2 (with the explicit value depending on the value of N f ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally apart from the first few coefficients of the beta functions, we know little about them. Therefore it's meaningful to study the large order behaviour of quantum field theory under some approximation [12][13][14][15]. An essential point, in the investigation of the large order behaviour of field theories, is whether the results obtained are convergent.…”
Section: Introductionmentioning
confidence: 99%